The effects of implanting Stilbestrol in feeder lambs and feeding a Stilbestrol premix to feeder lambs upon the quality and palatabillty of the carcass. - Mackintosh, D.L.; Soule, R.P. Jr.; Bell, T.D.; Hall, J.L.; Harrison, D.; Westerman, B. (Kansas Agricultural Experiment Station, 2011)
Diethylstilbestrol when implanted in growing fattening lambs increases the rate of gain and feeding efficiency, but lowers the yield and the carcass grade. These observations are accepted as a result of work done by several researchers at different experiment stations. None of these investigations made a complete analysis of the carcass; therefore this project was designed to procure additional information regarding the influence of stilbestrol upon the quality and palatability of the carcass.
Keywords: Sheep; Stilbestrol; Quality; Palatability